Ar–Ar dating for hydrothermal quartz from the 2.4 Ga Ongeluk Formation, South Africa: implications for seafloor hydrothermal circulation. Issue 9 (26th September 2018) - Saito, Takuya; Qiu, Hua-Ning; Shibuya, Takazo; Li, Yi-Bing; Kitajima, Kouki; Yamamoto, Shinji; Ueda, Hisahiro; Komiya, Tsuyoshi; Maruyama, Shigenori
Abstract : Fluid inclusions in hydrothermal quartz in the 2.4 Ga Ongeluk Formation, South Africa, are expected to partially retain a component of the ancient seawater. To constrain the origin of the fluid and the quartz precipitation age, we conducted Ar–Ar dating for the quartz via a stepwise crushing method. The obtained argon isotopes show two or three endmembers with one or two binary mixing lines as the crushing proceeds, suggesting that the isotopic compositions of these endmembers correspond to fluid inclusions of each generation, earlier generated smaller 40 Ar- and K-rich inclusions, moderate 40 Ar- and 38 ArCl (neutron-induced 38 Ar from Cl)-rich inclusions and later generated larger atmospheric-rich inclusions. The K-rich inclusions show significantly different 40 Ar/ 38 ArCl values compared to the 38 ArCl -rich inclusions, indicating that it is difficult to constrain the quartz formation age using only fluid inclusions containing excess 40 Ar. The highest obtained 40 Ar/ 36 Ar value from the fluid inclusions is consistent with an expected value of the Ongeluk plume source, suggesting that the quartz precipitation was driven by Ongeluk volcanism. Considering the fluid inclusion generations and their compositions, the hydrothermal system was composed of crustal fluid and magmatic fluid without seawater before the beginning of a small amount of seawater input to the hydrothermal system.